EXPANDING THE FUNCTIONAL CAPABILITIES OF THE INFORMATION TECHNOLOGYSOFTWARE MODULE FOR CLIENT RELATIONSHIP MANAGEMENT - KRYLIK, LYUDMILA; SHARGALO, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work is dedicated to expanding the functional capabilities of the Customer Relationship Management (CRM) software module. A client-server architecture was chosen for the implementation. The client side is developed using JavaScript and the React framework. Using React allows for the creation of a convenient and intuitive interface for client interaction. For the server side, Node.js was used. MongoDB, a document-oriented NoSQL database, was chosen for database management. This type of database is ideal for handling large volumes of data and offers flexibility in data storage structure. Visual Studio Code was selected as the development environment, which provides numerous advantages, including open-source code, ease of use, intelligent autocompletion, an integrated debugger, Git integration, and support for various extensions that significantly enhance development productivity. A modular approach was used in the development to ensure fast system performance and ease of future maintenance. To better understand the operation of the CRM software module, a UML sequence diagram was developed, which is an important part of the software development process. The development was successfully tested. It meets all the specified requirements and has extended functionality compared to similar systems, offering at least four key advantages: the presence of an integrated chat for fast communication with clients; the ability to add notes, which, unlike analogs, feature a simplified note-taking mechanism; an optimized interface, making the program faster and more intuitive to use; and a competitive price, making it attractive for small and medium-sized businesses. This extended functionality will contribute to improving customer relationship management efficiency. The developed software product, unlike its counterparts, occupies less server memory.
Keywords: customer relationship management; CRM; information technology; automation; personalization; data analysis